Factors Affecting Customers Choice of Life Insurance Companies in Nepal - Goet, Joginder (Nepalese Journal of Insurance and Social Security, 2022)
This research aims to examine the relationship between product and premium, service, closeness, technology, security, responsiveness, and brand image with customers’ choice of insurance companies and the impact of customers’ choice factors on customers’ choice of insurance companies. The research has used primary sources of data. A well-structured questionnaire was designed to collect data from 400 respondents. The convenience sampling technique was used to select a sample for the study. Moreover, Cronbach’s Alpha was assessed to test reliability. The correlational and causal research designs were used. The findings revealed a positive and significant relationship between customers’ choice factors with customers’ choice of life insurance companies. All the factors have a significant impact on the choice of life insurance companies except Product and Premium. This study is useful for those managers and insurance policymakers who want to achieve wider markets. This research suggests a model that enhances the above-mentioned factors through the choice of insurance company in Nepal.